Impact of Intimate Partners Violence Against Women on Immunization Status of Children in Bangladesh (Dhaka University Journal of Science, 2015)
Intimate partners violence has harmful effect on child immunization. There is evidence regarding a relation between intimate partners violence against women and immunization status of their children. To investigate this relation in Bangladesh, the data extracted from Bangladesh Demographic and Health Survey (BDHS) in 2007 is used and information from 1969 childrens mother selected from intimate partners violence module is utilized in this study. The analyses reveal that more than half of childrens mother experienced intimate partners violence and a considerable proportion of children aged 12-59 months are found not to be fully immunized. Intimate partners violence against women has strong significant effect on child immunization in unadjusted as well as adjusted models. DOI: http://dx.doi.org/10.3329/dujs.v63i1.21760 Dhaka Univ. J. Sci. 63(1): 9-14, 2015 (January)